Desenvolvimento, produção e qualidade de frutos de melancia sob adubação nitrogenada e Ethephon. - Figueredo, Lucimara Ferreira de (2020)
The production of watermelon has occupied an important place in the world agriculture, being that in Brazil it is one of the main cultivated vegetable species, being base of support for diverse rural properties. In this sense, an experiment was carried out from July to October 2016 and November 2016 to February 2017 at the State University of Paraíba, campus IV, Catolé do Rocha, to evaluate the effects of nitrogen and ethephon fertilization on gas exchange, fluorescence chlorophyll content, growth, phytomass, yield and ripening curve of watermelon fruits. The experimental design was in randomized blocks, with an experimental arrangement with pre-determined levels for the factors, through the “Plan Puebla III” matrix, with 10 treatments and a control (without fertilization), which consisted of 5 doses of N (9 ; 54; 90; 126 and 171 kg ha-1 ) and 5 doses of ethephon (30; 180; 300; 420 and 570 mg L-1 ), with three repetitions. N doses were equally divided and applied twice, 20 days after seeding (DAS) and 40 DAS. The application of ethephon was performed at 35 DAS. Gas exchange, chlorophyll a fluorescence and chlorophyll a, b and total indices were analyzed at 30 DAP, that is, at the beginning of flowering. Plant growth was evaluated every seven days from the first application of ethephon. At the end of each cycle, the plants were collected and the leaves, stems and roots were separated for the mass production of aerial dry matter (MSPA), root (MSR), total (MST) and the aerial part root ratio (R/PA). At 65 DAS, fruits were harvested. The total number of fruits per plot was determined; number of fruits per plant; production per plant; average fruit mass per plot and productivity. At 45 DAS and ten days after anthesis, the monitoring of the fruit growth curve began, totaling five evaluations at five-day intervals, with three fruits being harvested per treatment in a total of 33 fruits per period, to elaborate the ripening curve. The physical and chemical characteristics of the fruits were evaluated. At 65 DAS, the color of the skin and pulp, as well as the firmness of the fruits, were analyzed. The association between nitrogen and ethephon, as dependent factors, promotes higher levels of Ci, gs, A, E and EiC in the first season of watermelon plants cv. Crimson Sweet. In the second season, the highest doses of N and E increased the rates of Ci, E and EiUA. The photosynthetic characteristics of the watermelon show better results in the first season, with nitrogen doses in the range of 126 to 170 kg ha-1 , and ethephon doses between 420 and 570 mg L-1 . The ethephon regulates the assimilation of gas exchange, fluorescence of chlorophyll a, b and total in the culture of the watermelon in the first season, eventually to Ci, E, gs, A, EiC and EiUA. The use of ehtephon results in a better use in the culture of watermelon with assimilation of N, and the behavior of photosynthesis suggests that the factors allow to produce earlier fruits and accelerate the formation of fruits, being able to accelerate the ripening. Growth and production decreased with increasing doses of nitrogen and ethephon, inhibiting growth and production per plant in both seasons. The doses of N inhibited the dry mass of the aerial part and the total dry mass in the two growing seasons, however for the dry mass of the root and the aerial part ratio in the first growing season, nitrogen did not affect positively, however in the second season of cultivation the greatest gain of dry mass were verified in the doses of 113 and 100 kg ha-1 of N. The ethephon inhibited the dry mass of the aerial part and total in the two growing seasons, in turn, for the dry mass of the root in the two growing seasons, the highest doses of ethephon increased the dry mass of the root, whereas the ratio of the aerial part to the root in the first season of cultivation it did not differ statistically, in the second season the dose of 325 mg L-1 caused the highest ratio. The combination of 126 kg ha-1 of N and 570 mg L-1 of ethephon in the first growing season promoted the highest production per plant and the number of fruits per plot, in relation to the second growing season the highest levels of nitrogen and ethephon reduced production per plant and the number of fruits per plot. The doses of N and ethephon did not affect the average weight of the fruits and the productivity of fruits of melancieira cv. Crimson Sweet in the two growing seasons analyzed. The highest fruit mass, pulp and peel thickness were obtained in the first growing season with the doses 115,85 kg h-1 , 80,5 kg h-1 and 171 kg h -1 of N. The largest color of the pulp a* and chromium were obtained with the combination of 126 kg h-1 of N and 570 mg L-1 of ethephon. Soluble solids and chlorophyll content were also higher in the first growing season with doses of 171 kg h-1 and 90,14 kg h-1 of N. The longest fruit length was obtained in the second growing season with dose of 56.75 kg h-1 of N. The increasing doses of ethephon in the first season obtained the highest thickness of the pulp; shell color a*, b* and hue angle, and the chrome of the shell; pulp color L* and hue angle and chlorophyll content, however from the 68,33 mg L-1 dose of ethephon the soluble solids were reduced. In relation to the second season, greater results were obtained only for the pulp mass, firmness and color of the pulp angle b * at doses of 181,77 and 570 mg L-1 , respectively. The watermelon cultivated in the interior of Paraíba takes 65 days after sowing for its complete ripening regardless of the season studied.